High C-reactive protein is associated with increased risk of biochemical hypogonadism: a population-based cohort study - Amar Osmancevic; Kristin Ottarsdottir; Margareta Hellgren; Ulf Lindblad; Bledar Daka (Endocrine Connections, 2022)
Context: Obesity seems to decrease levels of testosterone. It is still unknown what role inflammation plays in the secretion of testosterone in men. Objective: The objective is to study the association between levels of C-reactive protein and testosterone and its role in predicting biochemical hypogonadism in men. Design: This was a longitudinal observational study between 2002 and 2014 in Sweden. Patients or other participants: At the first visit, a random population sample of 1400 men was included, and 645 men fulfilled a similar protocol at a 10-year follow-up visit. After exclusion, 625 men remained to be included in the final analyses. Main outcome measure(s): Serum concentrations of testosterone and C-reactive protein (CRP) were measured at both visits. Bioavailable testosterone was calculated. Biochemical hypogonadism was defined as total testosterone levels <8 nmol/L. Results: At the first visit and in the longitudinal analyses, a strong association was found between high levels of CRP and low levels of calculated bioavailable testosterone even after adjustments for age, waist–hip ratio, hypertension, smoking, type 2 diabetes, and leisuretime physical activity (B = −0.31, 95% CI −0.49 to −0.13, P = 0.001, B = −0.26, 95% CI −0.41 to −0.11, P = 0.001). Similarly, increase with one s .d. in CRP was associated with increased risk of having hypogonadism after adjustment in the final model (odds ratio (OR) 1.76, 95% CI 1.12–2.78, P = 0.015, OR 1.80, 95% CI 1.16–2.78, P =0.008). Conclusions: In this representative cohort of men in southwestern Sweden, high levels of CRP were longitudinally associated with low concentrations of calculated bioavailable testosterone and increased risk of biochemical hypogonadism.